How Instructional Leadership Supports and Influences Teacher Professional Development? - Hafizah, Aidah Nur; Kasmaini, Kasmaini (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This study investigates how instructional leadership supports teacher professional development and how it influences teachers’ motivation and classroom performance. Using a qualitative approach, data were collected through semi-structured interviews with three participants: a school principal, a senior teacher, and an early-career teacher. The findings show that instructional leadership is enacted through clear communication of instructional goals, participatory decision-making, consistent supervision, constructive feedback, and facilitation of professional development activities. These practices help teachers engage more deeply in professional learning and strengthen their instructional capacity. The results also reveal that supportive leadership enhances teacher motivation by providing recognition, emotional encouragement, and opportunities for autonomy, which in turn improves teachers’ confidence and classroom performance. The study concludes that strong instructional leadership plays a vital role in shaping teacher learning and motivation, ultimately contributing to improved instructional quality in schools. Recommendations include enhancing leaders’ coaching skills and strengthening collaborative learning structures to better support teacher development.